Experience of Psychiatric Mental Health Nurse Practitioners in Public Mental Health. Issue 3 (July 2016) - Phoenix, Bethany J.; Hurd, Manton; Chapman, Susan A.
Abstract : Expansion of health insurance coverage under the Accountable Care Act has meant that millions of people are now insured for mental health treatment, but with no significant increase in the mental health workforce. Services of psychiatric mental health nurse practitioners (PMHNPs) may be best utilized to improve access to and quality of public mental health services if the financial, political, scope of practice, and treatment model barriers that limit their ability or willingness to practice in these settings are better understood. This article reports qualitative results from a study that assessed barriers and best practices in the use of PMHNPs in county mental health services in California. Results indicate that PMHNPs are valued for their "whole person" perspective, collaborative approach, and interpersonal communication skills, but that significant knowledge gaps, regulatory constraints, and bureaucratic barriers in public mental health systems inhibit PMHNPs from practicing at the top of their scope.